Four new species and additional records of Palaearctic Sunius, with two new synonymies (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2008)
Four species of Sunius Stephens are described and illustrated: S. tronqueti sp. n. (Spain: Sierra Nevada), S. filabresicus sp. n. (Spain: Sierra de los Filabres), S. gadoricus sp. n. (Spain: Sierra de Gádor), and S. kastcheevi sp. n. (Kazakhstan). Two synonymies are proposed: S. melanocephalus (Fabricius, 1793) = S. anatolicus Assing, 1995, syn. n., S. claviceps (Reitter, 1908) = Sunius bogdoensis Grebennikov, 2001, syn. n. Additional records of 24 (sub-)species are reported from the Palaearctic region. Keywords Coleoptera, Staphylinidae, Paederinae, Sunius, Palaearctic region, taxonomy, new species, new synonymies, additional records. Nomenclatural Acts bogdoensis Grebennikov, 2001 (Sunius), syn. n. of Sunius claviceps (Reitter, 1908) filabresicus Assing, 2008 (Sunius), spec. n. gadoricus Assing, 2008 (Sunius), spec. n. kastcheevi Assing, 2008 (Sunius), spec. n. tronqueti Assing, 2008 (Sunius), spec. n.